Recyclable TPEE film and preparation method thereof

By adding diatomaceous earth-loaded nanotitanium dioxide to the TPEE film, and carrying out acid leaching and silane modification treatment, the problem of decreasing tensile strength and moisture permeability of the TPEE film after use is solved, and the recycling and service life of the film material is achieved.

CN119505489APending Publication Date: 2025-02-25KUNSHAN RED APPLE PLASTIC NEW MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411711746.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-14
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing TPEE films are difficult to maintain high tensile strength and moisture permeability after use, and are costly and difficult to achieve recycling.

Method used

By adding diatomaceous earth-loaded nanotitanium dioxide to the TPEE film and using acid leach and silane modification treatment, the light stability, moisture permeability and tensile strength of the film material can be improved, so that it can be recycled.

Benefits of technology

The TPEE film is achieved to maintain a high tensile strength and moisture permeability after use, extending its service life and reducing costs, so that the film material can be recycled.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a recyclable TPEE film and a preparation method thereof. The recyclable TPEE film is prepared from the following raw materials in parts by weight: 100 parts of TPEE resin master batch, 0.5 to 2.0 parts of cross-linking agent, 1.5 to 2.5 parts of antioxidant, 0.5 to 1.0 part of tackifier and 15 to 18 parts of diatomite loaded nano titanium dioxide. The recyclable TPEE film provided by the invention has relatively high moisture permeability and tensile strength retention rate, and can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a thermoplastic polyester elastomer material, and more specifically, to a recyclable TPEE film and a preparation method thereof. Background Art

[0002] TPEE is thermoplastic polyester elastomer, which is a block copolymer containing polyester hard segment and polyether soft segment. The polyether soft segment and the uncrystallized polyester form an amorphous phase, and the polyester hard segment partially crystallizes to form a crystalline micro-region, which acts as a physical cross-linking point. Therefore, TPEE has both the elasticity of rubber and the strength of engineering plastics. Films made of polyester materials can be used as packaging materials, printed composite films, capacitor films, etc. Since TPEE has the characteristics of both strength and elasticity, the use of TPEE to produce waterproof and breathable films for outdoor products or medical products has broad application prospects. However, waterproof and breathable films are generally made through physical or chemical breathability. If too much filler is added to hinder the passage of liquid, the elasticity of the film material will be reduced. If hydrophilic treatment is performed, hydrolysis will increase and the life of the film material will be reduced. Polyester film is relatively expensive. How to provide a TPEE film with breathable function that still maintains a high tensile strength after use so that the film material can be recycled is a problem to be solved. Summary of the invention

[0003] In order to solve the problem of recycling TPEE membranes, the present application provides a recyclable TPEE membrane and a preparation method thereof.

[0004] First, the present application provides a recyclable TPEE membrane, comprising the following components in parts by weight: 100 parts of TPEE resin masterbatch, 0.5-2.0 parts of a cross-linking agent, 1.5-2.5 parts of an antioxidant, 0.5-1.0 parts of a tackifier, and 15-18 parts of diatomaceous earth-loaded nano-titanium dioxide.

[0005] By adopting the above scheme, nano titanium dioxide has high stability, strong adhesion, good photocatalytic effect and ultraviolet shielding effect. By adding a certain mass of nano titanium dioxide to prepare TPEE film, nano titanium dioxide can improve the photostability of TPRR film, and can also decompose organic pollutants adsorbed on the film material, so that the service life of the film material with waterproof and moisture permeability effect is longer. Diatomaceous earth is light in weight, highly stable, and has more micropores. By loading nano TiO2 in the pores of diatomaceous earth, nano titanium dioxide is more stably adsorbed on the film material, and nano titanium dioxide photocatalytically degrades pollutants in the pores of diatomaceous earth to achieve in-situ regeneration of diatomaceous earth. The micropores of diatomaceous earth more stably maintain the waterproof and moisture permeability of the membrane material, improve the long-term stability of the pores of diatomaceous earth, and further improve the recyclability of the TPEE film.

[0006] In a specific embodiment, the mass ratio of the soft segment to the hard segment in the TPEE resin masterbatch is 3-8:2-9.

[0007] By adopting the above scheme, the mass distribution of the soft segment and the hard segment in the resin masterbatch is reasonable, the elasticity and strength of the prepared membrane material are appropriate, and it is suitable for use as a waterproof and breathable membrane. The diatomaceous earth-loaded nano-titanium dioxide can exist relatively stably in the membrane material matrix, and still has a high tensile strength after a period of use, and can be recycled.

[0008] In a specific possible implementation scheme, the process of diatomaceous earth loading nano-titanium dioxide comprises the following steps: ultrasonically dispersing nano-titanium dioxide in deionized water to obtain nano-titanium dioxide slurry, dispersing diatomaceous earth in deionized water to obtain diatomaceous earth slurry, adding the nano-titanium dioxide slurry to the diatomaceous earth slurry, continuously stirring during the adding process, and then ultrasonically dispersing to obtain a mixed solution, dehydrating and drying the mixed solution, and sieving to obtain diatomaceous earth loaded nano-titanium dioxide.

[0009] By adopting the above scheme, the preparation process is simple, nano-titanium dioxide is evenly loaded in the pores of diatomaceous earth, the prepared diatomaceous earth-loaded nano-titanium dioxide has uniform particle size and good compatibility with the membrane material, the prepared membrane material has good waterproof and moisture permeability effect, and can be recycled.

[0010] In a specific embodiment, the diatomaceous earth includes dodecyltrimethoxysilane-modified diatomaceous earth and methyltrimethoxysilane-modified diatomaceous earth.

[0011] By adopting the above scheme, the modified diatomaceous earth is more hydrophobic, the retention of water vapor in the membrane pores is reduced, and the service life of the membrane material is further improved. By limiting the diatomaceous earth to dodecyltrimethoxysilane modified diatomaceous earth and methyltrimethoxysilane modified diatomaceous earth, the long-term performance of the obtained membrane material is better. This may be because the methyl group forms a certain spatial steric hindrance, which protects the membrane material to a certain extent and reduces the hydrolysis of the membrane material. At the same time, the membrane material is more flexible and stable at this time. The hydroxyl groups on dodecyltrimethoxysilane and the abundant hydroxyl groups on dodecyltrimethoxysilane, methyltrimethoxysilane, and nano-titanium dioxide form hydrogen bonds, and the lines are entangled and the points are connected, which further improves the structural stability of the membrane material. The silane chain segment will not be too long to affect the moisture permeability and heat resistance of the membrane material, nor will it be too short to limit the protection of the membrane material. At this time, the number of methyl groups is also relatively appropriate, which has a good protective effect on the membrane material without affecting the moisture permeability.

[0012] In a specific embodiment, the mass ratio of dodecyltrimethoxysilane-modified diatomaceous earth to methyltrimethoxysilane-modified diatomaceous earth is 1:(1-1.1).

[0013] By adopting the above scheme, the structure of the membrane is relatively stable at this time, the long silane chain will not affect the moisture permeability and heat resistance of the membrane too much, nor will it be too little to limit the protection of the membrane. At this time, the number of methyl groups is also relatively appropriate, which has a good protection effect on the membrane without affecting the moisture permeability.

[0014] In one specific embodiment, the diatomaceous earth is acid leached.

[0015] By adopting the above scheme, the purity of the diatomaceous earth after acid leaching is higher, the density is lower, the pore volume and specific surface area are increased, the pore structure is more uniform, and the moisture permeability and durability of the prepared TPEE membrane are better.

[0016] In a specific embodiment, the fineness of the diatomaceous earth is 800-1200 mesh.

[0017] By adopting the above scheme, the fineness of diatomaceous earth can better load nano-titanium dioxide, and the pore size on the surface can better realize the waterproof and moisture permeability of the membrane material, without significantly increasing the hardness of the membrane material. The membrane material is relatively flexible and is not easily damaged after water vapor passes through. The prepared membrane material can be recycled for a long time.

[0018] In a specific embodiment, the soft segment of the TPEE resin masterbatch includes polytetramethylene terephthalate, and the hard segment includes polyethylene terephthalate.

[0019] By adopting the above scheme, the prepared membrane material is relatively flexible and can be recycled for a long time.

[0020] In a second aspect, the present application provides a method for preparing a recyclable TPEE membrane, comprising the following steps: weighing each component according to a mass ratio, mixing evenly, and then melt-extruding, casting, stretching, and winding to obtain the TPEE membrane.

[0021] By adopting the above scheme, the preparation method is relatively simple, and the prepared membrane material still has high tensile strength and good perspective after use, and can be recycled.

[0022] In a specific embodiment, the melt extrusion temperature is 265-280°C, and the stretching is first longitudinal stretching at a stretching temperature of 145-150°C and a stretching ratio of 1.2-2.0, and then transverse stretching at a stretching temperature of 130-145°C and a stretching ratio of 1.8-2.1.

[0023] By adopting the above scheme, the extrusion temperature is suitable for the components of the present application, the film material obtained after stretching is relatively uniform, and still has a high tensile strength after use.

[0024] In summary, this application has the following beneficial effects:

[0025] The present application adds a certain mass of diatomaceous earth loaded with nano-titanium dioxide into the TPEE membrane, and limits the mesh size of the diatomaceous earth to improve its compatibility with the membrane material, moisture permeability, and loading effect of nano-titanium dioxide. Nano-titanium dioxide decomposes organic pollution and shields the membrane material from ultraviolet rays, making the pores of the diatomaceous earth more durable and stable. The pore size of the diatomaceous earth is further adjusted by acid leaching, thereby extending the service life of the TPEE membrane, and the prepared TPEE membrane can be recycled.

[0026] The present application improves the hydrophobicity of diatomaceous earth and prolongs the service life of the membrane by subjecting diatomaceous earth to silane modification, limits the modification to dodecyltrimethoxysilane-modified diatomaceous earth and methyltrimethoxysilane-modified diatomaceous earth, and limits the mass ratio of the two, thereby improving the hydrophobicity of diatomaceous earth and extending the service life of the membrane, reducing the hydrolysis of the membrane by the steric hindrance of the methyl group, and improving the stability of the membrane by hydrogen bonding and chain segment entanglement. DETAILED DESCRIPTION

[0027] The TPEE masterbatch in the examples and comparative examples is Huisu HS-QY-9U-1, the crosslinking agent is diisopropylbenzene hydroperoxide, the antioxidant is antioxidant 1076, and the tackifier is KH570. The experimental reagents in the preparation examples, examples, and comparative examples, unless otherwise specified, are conventional commercial brands or obtained through conventional preparation processes.

[0028] Preparation Example

[0029] Preparation Example 1: Diatomaceous earth loaded with nano-titanium dioxide

[0030] 100 g of nano-titanium dioxide was ultrasonically dispersed at 300 W for 1 hour in 250 g of deionized water to obtain nano-titanium dioxide slurry, 200 g of diatomaceous earth was dispersed in 500 g of deionized water to obtain diatomaceous earth slurry, the nano-titanium dioxide slurry was added to the diatomaceous earth slurry with continuous stirring during the addition process, and then ultrasonically dispersed at 300 W for 1 hour to obtain a mixed solution, the mixed solution was dehydrated and dried at 60° C., and sieved through a 0.1 mm square hole sieve to obtain diatomaceous earth-loaded nano-titanium dioxide.

[0031] Preparation Example 2: Acid leaching of diatomaceous earth:

[0032] The hydrofluoric acid solution and the sulfuric acid solution were uniformly mixed to prepare a mixed acid solution with a hydrofluoric acid mass concentration of 12% and a sulfuric acid mass concentration of 60%. 100 g of diatomaceous earth was added to 650 g of the mixed acid solution, stirred evenly, filtered after 0.5 hour, then washed with deionized water until the pH was about 6.5, and dried to obtain acid-leached diatomaceous earth.

[0033] Preparation Example 3: Dodecyltrimethoxysilane modified diatomaceous earth:

[0034] 100 g of diatomaceous earth was added to 450 g of 20% ethanol aqueous solution by volume, and the mixture was stirred evenly. Then, 100 g of dodecyltrimethoxysilane was added, the pH value was adjusted to 2.5, nitrogen was introduced, and then the mixture was heated at 90° C. for 20 hours, filtered, washed, and dried to obtain dodecyltrimethoxysilane-modified diatomaceous earth.

[0035] Preparation Example 4: Methyltrimethoxysilane modified diatomaceous earth:

[0036] 100 g of diatomaceous earth was added to 450 g of 20% ethanol aqueous solution by volume, and the mixture was stirred evenly. Then, 100 g of methyltrimethoxysilane was added, the pH value was adjusted to 2.5, nitrogen was introduced, and then the mixture was heated at 90° C. for 12 hours, filtered, washed, and dried to obtain methyltrimethoxysilane-modified diatomaceous earth.

[0037] Preparation Example 5: Dodecyltrimethoxysilane-modified diatomaceous earth loaded with nano-titanium dioxide:

[0038] 100 g of nano-titanium dioxide was ultrasonically dispersed at 300 W for 1 hour in 250 g of deionized water to obtain nano-titanium dioxide slurry, 200 g of dodecyltrimethoxysilane-modified diatomaceous earth obtained in Preparation Example 3 was dispersed in 500 g of deionized water to obtain diatomaceous earth slurry, the nano-titanium dioxide slurry was added to the diatomaceous earth slurry, stirring was continued during the addition process, and then ultrasonically dispersed at 300 W for 1 hour to obtain a mixed solution, the mixed solution was dehydrated and dried at 60° C., and sieved with a 0.1 mm square hole sieve to obtain dodecyltrimethoxysilane-modified diatomaceous earth loaded with nano-titanium dioxide.

[0039] Preparation Example 6: Methyltrimethoxysilane-modified diatomaceous earth loaded with nano-titanium dioxide:

[0040] 100 g of nano-titanium dioxide was ultrasonically dispersed at 300 W for 1 hour in 250 g of deionized water to obtain nano-titanium dioxide slurry. 200 g of methyltrimethoxysilane-modified diatomaceous earth-loaded nano-titanium dioxide obtained in Preparation Example 4 was dispersed in 500 g of deionized water to obtain diatomaceous earth slurry. The nano-titanium dioxide slurry was added to the diatomaceous earth slurry with continuous stirring during the addition process, and then ultrasonically dispersed at 300 W for 1 hour to obtain a mixed solution. The mixed solution was dehydrated and dried at 60° C. and sieved with a 0.1 mm square hole sieve to obtain methyltrimethoxysilane-modified diatomaceous earth-loaded nano-titanium dioxide.

[0041] Preparation Example 7: Dodecyltrimethoxysilane modified acid-leached diatomaceous earth:

[0042] 100 g of the acid-leached diatomite obtained in Preparation Example 2 was added to 450 g of 20% ethanol aqueous solution by volume, stirred evenly, and then 100 g of dodecyltrimethoxysilane was added, the pH value was adjusted to 2.5, nitrogen was introduced, and then heated at 90° C. for 20 hours, filtered, washed, and dried to obtain dodecyltrimethoxysilane-modified acid-leached diatomite.

[0043] Preparation Example 8: Methyltrimethoxysilane modified acid-leached diatomaceous earth:

[0044] 100 g of the acid-leached diatomite obtained in Preparation Example 2 was added to 450 g of 20% ethanol aqueous solution by volume, stirred evenly, and then 100 g of methyltrimethoxysilane was added, the pH value was adjusted to 2.5, nitrogen was introduced, and then heated at 90° C. for 12 hours, filtered, washed, and dried to obtain methyltrimethoxysilane-modified acid-leached diatomite.

[0045] Preparation Example 9: Dodecyltrimethoxysilane modified acid-leached diatomaceous earth loaded with nano-titanium dioxide:

[0046] 100 g of nano-titanium dioxide was ultrasonically dispersed at 300 W for 1 hour in 250 g of deionized water to obtain nano-titanium dioxide slurry. 200 g of methyltrimethoxysilane-modified acid-leached diatomite-loaded nano-titanium dioxide obtained in Preparation Example 7 was dispersed in 500 g of deionized water to obtain diatomite slurry. The nano-titanium dioxide slurry was added to the diatomite slurry with continuous stirring during the addition process. The mixture was then ultrasonically dispersed at 300 W for 1 hour to obtain a mixed solution. The mixed solution was dehydrated and dried at 60° C. and sieved with a 0.1 mm square hole sieve to obtain methyltrimethoxysilane-modified acid-leached diatomite-loaded nano-titanium dioxide.

[0047] Preparation Example 10: Methyltrimethoxysilane modified acid-leached diatomaceous earth loaded with nano-titanium dioxide:

[0048] 100 g of nano-titanium dioxide was ultrasonically dispersed at 300 W for 1 hour in 250 g of deionized water to obtain nano-titanium dioxide slurry. 200 g of methyltrimethoxysilane-modified acid-leached diatomite-loaded nano-titanium dioxide obtained in Preparation Example 8 was dispersed in 500 g of deionized water to obtain diatomite slurry. The nano-titanium dioxide slurry was added to the diatomite slurry with continuous stirring during the addition process. The mixture was then ultrasonically dispersed at 300 W for 1 hour to obtain a mixed solution. The mixed solution was dehydrated and dried at 60° C. and sieved with a 0.1 mm square hole sieve to obtain methyltrimethoxysilane-modified acid-leached diatomite-loaded nano-titanium dioxide.

[0049] Preparation Example 11: Methyltrimethoxysilane modified acid-leached diatomaceous earth loaded with nano-silica:

[0050] 100 g of nano-silica was ultrasonically dispersed at 300 W for 1 hour in 250 g of deionized water to obtain nano-silica slurry, 200 g of methyltrimethoxysilane-modified acid-leached diatomite obtained in Preparation Example 8 was dispersed in 500 g of deionized water to obtain diatomite slurry, the nano-silica slurry was added to the diatomite slurry, stirring was continued during the addition process, and then ultrasonically dispersed at 300 W for 1 hour to obtain a mixed solution, the mixed solution was dehydrated and dried at 60° C., and sieved with a 0.1 mm square hole sieve to obtain methyltrimethoxysilane-modified acid-leached diatomite loaded with nano-silica.

[0051] Preparation Example 12: Acid-leached diatomaceous earth loaded with nano-titanium dioxide:

[0052] 100 g of nano-titanium dioxide was ultrasonically dispersed at 300 W for 1 hour in 250 g of deionized water to obtain nano-titanium dioxide slurry, 200 g of the acid-leached diatomaceous earth obtained in Preparation Example 2 was dispersed in 500 g of deionized water to obtain diatomaceous earth slurry, the nano-titanium dioxide slurry was added to the diatomaceous earth slurry, stirring was continued during the addition process, and then ultrasonically dispersed at 300 W for 1 hour to obtain a mixed solution, the mixed solution was dehydrated and dried at 60° C., and sieved with a 0.1 mm square hole sieve to obtain acid-leached diatomaceous earth-loaded nano-titanium dioxide.

[0053] Example

[0054] Example 1

[0055] This example includes the following raw materials: 1000 g of TPEE resin masterbatch, 10 g of cross-linking agent, 15 g of antioxidant, 5 g of tackifier, and 180 g of diatomaceous earth-loaded nano-titanium dioxide obtained in Preparation Example 1.

[0056] Each component is weighed according to the mass ratio, mixed evenly, and then melt-extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 270°C, and the stretching is first longitudinal stretching, the stretching temperature is 145°C, the stretching ratio is 1.5, and then transverse stretching, the stretching temperature is 145°C, and the stretching ratio is 1.8.

[0057] Example 2

[0058] This example includes the following raw materials: 1000 g of TPEE resin masterbatch, 20 g of cross-linking agent, 25 g of antioxidant, 10 g of tackifier, and 150 g of diatomaceous earth-loaded nano-titanium dioxide obtained in Preparation Example 1.

[0059] Each component is weighed according to the mass ratio, mixed evenly, and then melt-extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 280°C, and the stretching is first longitudinal stretching, the stretching temperature is 150°C, the stretching ratio is 2.0, and then transverse stretching, the stretching temperature is 145°C, and the stretching ratio is 1.8.

[0060] Example 3

[0061] This example includes the following raw materials: 1000 g of TPEE resin masterbatch, 20 g of cross-linking agent, 15 g of antioxidant, 5 g of tackifier, and 180 g of diatomaceous earth-loaded nano-titanium dioxide obtained in Preparation Example 1.

[0062] Each component is weighed according to the mass ratio, mixed evenly, and then melt extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 270°C, and the stretching is first longitudinal stretching, the stretching temperature is 145°C, the stretching ratio is 1.5, and then transverse stretching, the stretching temperature is 130°C, and the stretching ratio is 2.1.

[0063] Example 4

[0064] This example contains the following raw materials: 1000 g of TPEE resin masterbatch, 10 g of cross-linking agent, 15 g of antioxidant, 5 g of tackifier, 90 g of dodecyltrimethoxysilane-modified diatomaceous earth-loaded nano-titanium dioxide prepared in Preparation Example 5, and 90 g of methyltrimethoxysilane-modified diatomaceous earth-loaded nano-titanium dioxide prepared in Preparation Example 6.

[0065] Each component is weighed according to the mass ratio, mixed evenly, and then melt-extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 270°C, and the stretching is first longitudinal stretching, the stretching temperature is 145°C, the stretching ratio is 1.5, and then transverse stretching, the stretching temperature is 145°C, and the stretching ratio is 1.8.

[0066] Example 5

[0067] This example contains the following raw materials: 1000 g of TPEE resin masterbatch, 10 g of cross-linking agent, 15 g of antioxidant, 5 g of tackifier, 80 g of dodecyltrimethoxysilane-modified diatomaceous earth-loaded nano-titanium dioxide prepared in Preparation Example 5, and 100 g of methyltrimethoxysilane-modified diatomaceous earth-loaded nano-titanium dioxide prepared in Preparation Example 6.

[0068] Each component is weighed according to the mass ratio, mixed evenly, and then melt-extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 270°C, and the stretching is first longitudinal stretching, the stretching temperature is 145°C, the stretching ratio is 1.5, and then transverse stretching, the stretching temperature is 145°C, and the stretching ratio is 1.8.

[0069] Example 6

[0070] This example contains the following raw materials: 1000 g of TPEE resin masterbatch, 10 g of cross-linking agent, 15 g of antioxidant, 5 g of tackifier, and 180 g of methyltrimethoxysilane-modified diatomaceous earth loaded with nano-titanium dioxide obtained in Preparation Example 6.

[0071] Each component is weighed according to the mass ratio, mixed evenly, and then melt-extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 270°C, and the stretching is first longitudinal stretching, the stretching temperature is 145°C, the stretching ratio is 1.5, and then transverse stretching, the stretching temperature is 145°C, and the stretching ratio is 1.8.

[0072] Example 7

[0073] This example contains the following raw materials: 1000 g of TPEE resin masterbatch, 10 g of cross-linking agent, 15 g of antioxidant, 5 g of tackifier, 90 g of dodecyltrimethoxysilane-modified acid-leached diatomaceous earth loaded with nano-titanium dioxide prepared in Preparation Example 9, and 90 g of methyltrimethoxysilane-modified acid-leached diatomaceous earth loaded with nano-titanium dioxide prepared in Preparation Example 10.

[0074] Each component is weighed according to the mass ratio, mixed evenly, and then melt-extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 270°C, and the stretching is first longitudinal stretching, the stretching temperature is 145°C, the stretching ratio is 1.5, and then transverse stretching, the stretching temperature is 145°C, and the stretching ratio is 1.8.

[0075] Example 8

[0076] This example contains the following raw materials: 1000 g of TPEE resin masterbatch, 10 g of cross-linking agent, 15 g of antioxidant, 5 g of tackifier, and 180 g of acid-leached diatomaceous earth loaded with nano-titanium dioxide obtained in Preparation Example 12.

[0077] Each component is weighed according to the mass ratio, mixed evenly, and then melt-extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 270°C, and the stretching is first longitudinal stretching, the stretching temperature is 145°C, the stretching ratio is 1.5, and then transverse stretching, the stretching temperature is 145°C, and the stretching ratio is 1.8.

[0078] Comparative Example

[0079] Comparative Example 1

[0080] This embodiment includes the following raw materials: 1000 g of TPEE resin masterbatch, 10 g of cross-linking agent, 15 g of antioxidant, 5 g of tackifier, 100 g of diatomaceous earth, and 80 g of nano titanium dioxide.

[0081] Each component is weighed according to the mass ratio, mixed evenly, and then melt-extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 270°C, and the stretching is first longitudinal stretching, the stretching temperature is 145°C, the stretching ratio is 1.5, and then transverse stretching, the stretching temperature is 145°C, and the stretching ratio is 1.8.

[0082] Comparative Example 2

[0083] This example contains the following raw materials: 1000 g of TPEE resin masterbatch, 10 g of a cross-linking agent, 15 g of an antioxidant, 5 g of a tackifier, and 180 g of methyltrimethoxysilane-modified acid-leached diatomaceous earth loaded with nano-silica obtained in Preparation Example 11.

[0084] Each component is weighed according to the mass ratio, mixed evenly, and then melt-extruded, cast, stretched, and rolled to obtain the TPEE film. The temperature of the melt extrusion is 270°C, and the stretching is first longitudinal stretching, the stretching temperature is 145°C, the stretching ratio is 1.5, and then transverse stretching, the stretching temperature is 145°C, and the stretching ratio is 1.8.

[0085] Performance testing

[0086] Test 1: Referring to the standard GB 1037-1988, the water vapor transmission rate tester W3 / 031 was used to test the water vapor permeability of the TPEE films prepared in each embodiment and comparative example. The test results are summarized in Table 1;

[0087] Test 2: Referring to standard ASTM412, the tensile strength of the TPEE membranes prepared in the embodiments and comparative examples after 24 hours and 72 hours of moisture permeation was tested, and the change rate of tensile strength was calculated. The tensile strength retention rate = 72-hour tensile strength / 24-hour tensile strength × 100%. The test results are summarized in Table 1.

[0088] Table 1 <![CDATA[Water vapor permeability (g / m 2 ×24 h)]]> 24-hour tensile strength (MPa) Tensile strength retention rate (%) Example 1 4169.4 47.5 96.7 Example 2 4160.5 47.1 96.9 Example 3 4173.3 47.3 96.8 Example 4 4133.3 58.4 98.7 Example 5 4143.6 52.0 98.4 Example 6 4150.1 48.1 97.5 Example 7 4183.4 49.7 99.3 Example 8 4180.2 45.1 96.9 Comparative Example 1 3997.8 40.2 88.1 Comparative Example 2 4164.8 37.6 83.5

[0089] In combination with Examples 1-3, Comparative Examples 1-2 and Table 1, the present application adds a certain mass of diatomaceous earth loaded with nano-titanium dioxide into the TPEE membrane to obtain a waterproof and moisture-permeable membrane material with high tensile strength. It still maintains a high tensile strength after long-term use and can be recycled.

[0090] In combination with Example 1, Examples 4-6 and Table 1, the present application modifies diatomaceous earth with dodecyltrimethoxysilane and methyltrimethoxysilane and limits the mass ratio of the two, so that the film material obtained has high tensile strength and high tensile strength retention rate after long-term use.

[0091] In combination with Example 1, Example 8, Example 4, Example 7 and Table 1, the present application performs acid leaching on diatomaceous earth to obtain a membrane material with better moisture permeability, and the membrane material modified with silane after acid leaching has the best overall performance.

[0092] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A recyclable TPEE film, characterized in that: The TPEE film comprises the following raw materials in parts by weight: 100 parts of TPEE resin masterbatch, 0.5-2.0 parts of a cross-linking agent, 1.5-2.5 parts of an antioxidant, 0.5-1.0 parts of a tackifier, and 15-18 parts of diatomaceous earth-loaded nano-titanium dioxide.

2. The recyclable TPEE film according to claim 1, characterized in that: The mass ratio of the soft segment to the hard segment in the TPEE resin masterbatch is 3-8:2-9.

3. The recyclable TPEE film according to claim 1, characterized in that: The process of diatomaceous earth loading nano-titanium dioxide comprises the following steps: ultrasonically dispersing nano-titanium dioxide in deionized water to obtain nano-titanium dioxide slurry, dispersing diatomaceous earth in deionized water to obtain diatomaceous earth slurry, adding the nano-titanium dioxide slurry to the diatomaceous earth slurry, continuously stirring during the adding process, then ultrasonically dispersing to obtain a mixed solution, dehydrating and drying the mixed solution, and sieving to obtain diatomaceous earth loaded titanium dioxide.

4. The recyclable TPEE film according to claim 1, characterized in that: The diatomaceous earth includes dodecyltrimethoxysilane-modified diatomaceous earth and methyltrimethoxysilane-modified diatomaceous earth.

5. The recyclable TPEE film according to claim 4, characterized in that: The mass ratio of the dodecyltrimethoxysilane-modified diatomaceous earth to the methyltrimethoxysilane-modified diatomaceous earth is 1:(1-1.1).

6. The recyclable TPEE film according to claim 1, characterized in that: The diatomaceous earth is acid leached.

7. The recyclable TPEE film according to claim 1, characterized in that: The fineness of the diatomaceous earth is 800-1200 meshes.

8. The recyclable TPEE film according to claim 1, characterized in that: The soft segment of the TPEE resin masterbatch includes polytetramethylene terephthalate, and the hard segment includes polyethylene terephthalate.

9. A method for preparing a recyclable TPEE membrane according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: weighing each component according to a mass ratio, mixing them evenly, then melting and extruding, casting, stretching and rolling up to obtain a TPEE film.

10. The method for preparing a recyclable TPEE film according to claim 9, characterized in that: The temperature of the melt extrusion is 265-280° C., and the stretching is first longitudinal stretching at a stretching temperature of 145-150° C. and a stretching ratio of 1.2-2.0, and then transverse stretching at a stretching temperature of 130-145° C. and a stretching ratio of 1.8-2.1.

Citation Information

Cited By

  • TPEE composite material as well as preparation method and application thereof

    CN121450068A

  • A TPEE composite material, its preparation method and application

    CN121450068B